What works best for whom? Cognitive Behavior Therapy and Mindfulness-Based Cognitive Therapy for depressive symptoms in patients with diabetes. - K Annika Tovote; Maya J Schroevers; Evelien Snippe; Paul M G Emmelkamp; Thera P Links; Robbert Sanderman; Joke Fleer (PLoS ONE, 2017)
Cognitive Behavior Therapy (CBT) and Mindfulness-Based Cognitive Therapy (MBCT) have shown to be effective interventions for treating depressive symptoms in patients with diabetes. However, little is known about which intervention works best for whom (i.e., moderators of efficacy). The aim of this study was to identify variables that differentially predicted response to either CBT or MBCT (i.e., prescriptive predictors).The sample consisted of 91 adult outpatients with type 1 or type 2 diabetes and comorbid depressive symptoms (i.e., BDI-II ≥ 14) who were randomized to either individual 8-week CBT (n = 45) or individual 8-week MBCT (n = 46). Patients were followed for a year and depressive symptoms were measured at pre-treatment, post-treatment, and at 9-months follow-up. The predictive effect of demographics, depression related characteristics, and disease specific characteristics on change in depressive symptoms was assessed by means of hierarchical regression analyses.Analyses showed that education was the only factor that differentially predicted a decrease in depressive symptoms directly after the interventions. At post-treatment, individuals with higher educational attainment responded better to MBCT, as compared to CBT. Yet, this effect was not apparent at 9-months follow-up.This study did not identify variables that robustly differentially predicted treatment effectiveness of CBT and MBCT, indicating that both CBT and MBCT are accessible interventions that are effective for treating depressive symptoms in broad populations with diabetes. More research is needed to guide patient-treatment matching in clinical practice.